2007
DOI: 10.1063/1.2733656
|View full text |Cite
|
Sign up to set email alerts
|

Role of template layer on microstructure, phase formation and polarization behavior of ferroelectric relaxor thin films

Abstract: Articles you may be interested inSignificant enhancement of energy-storage performance of (Pb0.91La0.09)(Zr0.65Ti0.35)O3 relaxor ferroelectric thin films by Mn doping ͑1−x͒Pb͑Mg 1/3 Nb 2/3 ͒O 3 − ͑x͒PbTiO 3 ͑PMNPT͒ a relaxor ferroelectric has gained attention due to its interesting physical properties both in the bulk and thin film forms from a technological and fundamental point of view. The PMNPT solid solution at the morphotropic phase boundary composition has superior properties and is potentially used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…11 So-called 'buffer layers' between the ferroelectric film and platinized silicon substrate modify the residual stress state 12,13 which has a significant effect on the ferroelectric, piezoelectric and dielectric properties and, along with 'seed-layers', have been used to control film orientation. 14,15 In addition, to the use of buffer and seed layers, it has been known for many years that oxide electrodes used instead of plantinum (Pt on Ti/SiO2/Si) improve performance since they prevent undesired compositional modification and impede charge interdiffusion processes. [16][17][18][19] Table I describes some examples of the effect of interlayers on ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 So-called 'buffer layers' between the ferroelectric film and platinized silicon substrate modify the residual stress state 12,13 which has a significant effect on the ferroelectric, piezoelectric and dielectric properties and, along with 'seed-layers', have been used to control film orientation. 14,15 In addition, to the use of buffer and seed layers, it has been known for many years that oxide electrodes used instead of plantinum (Pt on Ti/SiO2/Si) improve performance since they prevent undesired compositional modification and impede charge interdiffusion processes. [16][17][18][19] Table I describes some examples of the effect of interlayers on ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%
“…So-called “seed layers” are known to control perovskite nucleation, reduce the temperature of phase formation, improve the film crystalline degree, suppress the formation of planar defects, and prevent reaction between films and substrates. Seed layers have been extensively used on Pt/Ti/SiO 2 /Si bottom electrodes to overcome the detrimental effects of microstructural heterogeneities and variations in the crystalline quality of the films and are known to prevent deterioration of the ferroelectric properties . So-called “buffer layers” between the ferroelectric film and platinized silicon substrate modify the residual stress state , which has a significant effect on the ferroelectric, piezoelectric, and dielectric properties and, along with “seed-layers”, have been used to control film orientation. , In addition to the use of buffer and seed layers, it has been known for many years that oxide electrodes used instead of plantinum (Pt on Ti/SiO 2 /Si) improve performance since they prevent undesired compositional modification and impede charge interdiffusion processes. Table describes some examples of the effect of interlayers on ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several deposition techniques for fabricating oxide electrodes or buffer layers such as laser ablation, sputtering, and sol-gel [17][18][19]. Tang et al have shown that PCT thin films on LaNiO 3 coated fused quartz and Si substrates maintain good dielectric and ferroelectric properties [20].…”
Section: Introductionmentioning
confidence: 99%